1986
DOI: 10.1021/bi00368a014
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of nicotinamide adenine dinucleotide in normal and xeroderma pigmentosum fibroblast cells by the antitumor drug CC-1065

Abstract: CC-1065 is an extremely potent antitumor antibiotic that forms a well-defined adduct with DNA in which the molecule lies within the minor groove and is covalently attached through N3 of adenine. Addition of CC-1065 to human fibroblast cells produced a prolonged depletion of the nicotinamide adenine dinucleotide (NAD) pool even at extremely low drug concentrations (0.01 microgram/mL). The depletion of NAD by CC-1065 was blocked by 3-aminobenzamide, which is consistent with a NAD depletion mechanism involving po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In support of this notion, NAD ϩ biosynthesis pathway has recently become a target for innovative therapy. 41,42 Indeed a chemical inhibitor of Nampt induces cell death in several types of human cancers. Importantly, the consequences of Nampt inhibition in healthy PBMCs as well as in CD34 ϩ hematopoietic progenitors 26 are less deleterious, indicating a favorable therapeutic window.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion, NAD ϩ biosynthesis pathway has recently become a target for innovative therapy. 41,42 Indeed a chemical inhibitor of Nampt induces cell death in several types of human cancers. Importantly, the consequences of Nampt inhibition in healthy PBMCs as well as in CD34 ϩ hematopoietic progenitors 26 are less deleterious, indicating a favorable therapeutic window.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Jacobson et al (1986) recently found that Xeroderma pigmentosum cells, which are deficient in repair of UV-induced and polycyclic carbon induced DNA damage (Hanawalt et al, 1987), show normal nicotinamide adenine dinucleotide depletion as normal human cells after CC-1065 treatment. These results indicate that in human cells there are different repair pathways for repairing UVand CC-1065-induced DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Novel approaches to circumvent tumor cell resistance mechanisms are therefore required and, in this context, several anticancer agents have recently been described that induce cell death by manipulating cellular energy stores. Indeed, intracellular depletion of nicotinamide adenine dinucleotide (NAD) and adenosine triphosphate (ATP) exerts strong cytolytic effects, [1][2][3][4][5][6][7][8] and the antitumor agent APO866 (previously called FK866 or WK175) is reported to induce cell death by reducing intracellular NAD content. 9,10 NAD plays a crucial role as a cofactor/substrate in numerous biochemical and biologic processes, including those catalyzed by poly(ADP-ribose) polymerase 1 (PARP1), sirtuins, and ADP-ribosyl cyclase 1-6.…”
Section: Introductionmentioning
confidence: 99%